Dinuclear Manganese Complexes Containing Chiral 1,4,7-Triazacyclononane-Derived Ligands and Their Catalytic Potential for the Oxidation of Olefins, Alkanes, and Alcohols - Romakh, Vladimir B.; Therrien, Bruno; Süss-Fink, Georg; Shul'pin, Georgiy B. (My University, 2007)
Five new 1,4,7-triazacyclononane-derived compds., sodium 3-(4,7-dimethyl-1,4,7-triazacyclononan-1-yl)propionate (Na[LMe2R']) as well as enantiopure (S)-1-(2-methylbutyl)-4,7-dimethyl-1,4,7-triazacyclononane (S-LMe2R''), (S,S)-trans-2,5,8-trimethyl-2,5,8-triazabicyclo[7.4.01,9]tridecane ((S,S)-LBMe3), (S)-1-(2-hydroxypropyl)-4,7-dimethyl-1,4,7-triazacyclononane (S-LMe2R), and (R)-1-(2-hydroxypropyl)-4,7-dimethyl-1,4,7-triazacyclononane (R-LMe2R), were synthesized. Reaction of MnCl2 with the chiral macrocycles S-LMe2R and R-LMe2R in aq. EtOH gives, upon oxidn. with H2O2, the brown dinuclear Mn(III)-Mn(IV) complexes which are enantiomers, [Mn2(S-LMe2R)2(?-O)2]3+ (S,S-1) and [Mn2(R-LMe2R)2(?-O)2]3+ (R,R-1). The single-crystal x-ray structure analyses of [S,S-1][PF6]3·0.5Me2CO and [R,R-1][PF6]3·0.5Me2CO show both enantiomers to contain Mn(III) and Mn(IV) centers, each of which being coordinated to three N atoms of a triazacyclononane ligand and each of which being bridged by two oxo and by two chiral hydroxypropyl pendent arms of the macrocycle. The enantiomeric complexes S,S-1 and R,R-1 catalyze the oxidn. of olefins, alkanes, and alcs. with H2O2. In the epoxidn. of indene the enantiomeric excess values attain 13%. The bond selectivities of the oxidn. of linear and branched alkanes suggest the crucial step in this process to be the attack of a sterically hindered high-valent Mn-oxo species on the C-H bond. [on SciFinder(R)]
Keywords: crystal structure manganese oxo chiral hydroxypropyl triazacyclononane dinuclear complex; manganese chiral triazacyclononane deriv prepn catalyst oxidn org substrate; asym epoxidn catalyst manganese chiral triazacyclononane deriv